PERANAN KELOMPOK PETERNAK SAPI POTONG DENGAN PENDEKATAN SISTEM INTEGRASI PADI TERNAK (SIPT) DI NUSA TENGGARA BARAT, JAWA TIMUR, DAN JAWA BARAT - MUSLIM, CHAIRUL (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Cattle development program, such as SIPT activity, has been implemented since 2002 in 11 province. In 2003, as its realization, cattle population has reached 2000 heads. This SIPT activity is an effort to increase cattle production, as well as food production through cattle raising activities in irrigated food crop land agro ecosystem zone. The base of the program is food crop and cattle production activities with Zero Waste Base. The objective of this research is to study how far the role of cattle raiser groups in implementing SIPT program is and its impact on SIPT non participant cattle raisers in West Nusa Tenggara, East Java, and West Java. The results of this study show that the role of cattle raiser groups in implementing SIPT activities varies with the development condition in each region. In general, the cattle raiser groups have implemented and have taken the benefit of the goals and basic concept of SIPT. Nevertheless, there are still some constrains and failures, such as not maximally use of hay as cattle feed and not optimally use of collective cattle cage. In the future, government, especially local government, should be more serious in creating conducive environment, such as good investment service and high attention to livestock development, especially cattle development.
Keywords: Cattle Raiser Groups, SIPT Program, NTB, East Java, West Java